(untitled) (Al-Farooq Journal of Sciences, 2026)
The study aimed to highlight the role of artificial intelligence in developing the labor market and achieving sustainable development, while emphasizing the importance of vocational training and professional development programs in preparing the workforce to cope with modern digital and technological transformations. The study adopted the descriptive-analytical approach through reviewing and analyzing literature and previous studies related to artificial intelligence, vocational training, and the future labor market. The findings revealed that artificial intelligence has become one of the most influential factors in reshaping jobs and professions, which necessitates developing workers’ technical and professional skills in line with the requirements of the digital economy. The results also showed that continuous training and vocational qualification contribute to improving human resource efficiency and enhancing adaptability to technological changes, in addition to promoting innovation and productivity within institutions. The study recommended developing educational curricula, supporting specialized training programs in artificial intelligence, and strengthening investment in scientific research and digital transformation to achieve a sustainable labor market based on knowledge and technology.